Artificial intelligence: past, present and future (2021)
Artificial Intelligence (AI) can be defined as the automatic (i.e. without human intervention) making of decisions to solve a specific problem within a specific given situation. This work looks at the evolution of artificial intelligence from the advances it brought and the struggles it faced in its early beginnings to the most recent successes and the renewed interest they ignited in present days. The scientific and technological foundation of the field will be overviewed. The influence of the dramatic increase in computational power will be discussed, together with the effect of the availability of cheap and accurate data at an unprecedented level and how it fueled the latest AI revolution. We will conclude with a glimpse of what is yet to come or is already there but still unnoticed: the very serious implications this technology will have at a societal level and the real threat it already poses to privacy